Czas usiłowania i dokonania kradzieży w sklepie samoobsługowym - Tyburcy, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
If the place where the theft was committed is a supermarket, establishing the precise time of that attempt is often disputed. It depends on the acceptance of a certain theoretical view about the notion of “an attempt.” According to the dominant position adopted in the Polish legal literature, theft is committed at the time of seizing the property, even before approaching the cash register.
Keywords: kradzież; sprzeniewierzenie; usiłowanie; komisja